PANDEMICS AND PUBLIC VALUE MANAGEMENT - Chohan, Usman W. ([S.l.] : ROUTLEDGE, 2022)
Widespread crisis-events such as pandemics can impose an immense strain on societies' multi-stakeholder efforts to preserve and sustain the mechanisms of public value (PV) creation. The global coronavirus (Covid-19) pandemic exemplifies this because it has pushed civil society, public managers, politicians, and society-at-large into uncharted waters, and at times brought them under exceptional duress. Then how can public value's agents attempt to conceive, create, and preserve value under such disruptive circumstances? How could public value theory's (PVT's) theoretical precepts be informed by the pandemic? This book seeks to inform the PVT literature by drawing upon interesting lenses that have emerged in the wake of the coronavirus pandemic. It addresses PVT's notions of value conflicts, post-Truth politics, multilateral PV, nationalism and the public, comparative PV creation, and PV in developing-country contexts, in order to construct a multi-stakeholder and internationally informed set of analyses on public value's systems and agents in uniquely distressing circumstances such as pandemics. This book will therefore be of use to both academics and practitioners of public administration and public policy, as well as scholars of government, healthcare policy, and economics.
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 Pandemic, 2020- -- Social aspects; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership; POLITICAL SCIENCE / Public Affairs & Administration